2005
DOI: 10.1111/j.1525-1438.2005.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Incisional skin metastasis of a squamous cell cervical carcinoma 3.5 years after radical treatment-a case report

Abstract: Metastatic carcinoma in an abdominal wall incision from internal malignant neoplasm is an uncommon and often a preterminal event. Most commonly metastatic skin incisional cancers have been reported with cancers of colon, kidney, and bladder. Incisional metastasis from postoperative case of carcinoma cervix is very rare. It has been reported in few patients with adenocarcinoma and poorly differentiated histopathology, more so at drain site postoperatively. We report a postoperative case of squamous cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Rarely (0.1–1.3%), metastatic recurrence of squamous cervical carcinoma could be identified in the abdominal wall especially in sites of incision [1]. Metastatic skin incisional cancers are usually presenting in cases of adenocarcinomas of the ovaries, colon, pancreas, kidneys, or bladder [2]. Based on the common metastasis of such adenocarcinomas, one could understand the possible mechanism of cervical adenocarcinomas; however, it is difficult to clarify the mechanism in squamous cell carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Rarely (0.1–1.3%), metastatic recurrence of squamous cervical carcinoma could be identified in the abdominal wall especially in sites of incision [1]. Metastatic skin incisional cancers are usually presenting in cases of adenocarcinomas of the ovaries, colon, pancreas, kidneys, or bladder [2]. Based on the common metastasis of such adenocarcinomas, one could understand the possible mechanism of cervical adenocarcinomas; however, it is difficult to clarify the mechanism in squamous cell carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Skin metastases from cervical carcinoma occur predominantly in cases of tumor recurrences [3]. A review of literature shows that most of skin metastases occurred after an interval less than 21 months except three cases reported by Behtash et al [3], Selo-Ojema et al [9], Srivastava et al [10] although the second case was adenocarcinoma of the cervix. In the present case, the patient developed umbilical metastasis without prior laparascopy or laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Skin involvement was observed directly, so that deduction concerning its mechanism ought to be reliable and have applicability to the general question of the mode of spread of cervical cancer. The mechanism of involvement was thought to be retrograde lymphatic spread from the corresponding regional lymph nodes [10]. This Wnding seemed important because it emphasized the predominant role of lymphatics in the spread of cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This case, however, is distinctive for several reasons. First, in prior reports of cutaneous metastases from cervical squamous cell carcinoma, the grossly visible nodules are usually single or a small cluster of multiple papules [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In our patient's case, the cutaneous metastases were innumerable and located diffusely over the anterior abdominal wall, vulva, perineum, and bilateral proximal lower extremities (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This clinical scenario is even less common in literature originating from the United States, due to the lower overall incidence of cervical cancer [3][4][5] . Case reports have documented various sites of cutaneous metastases, including the face and neck [6] , scalp [7][8][9] , vulva [5,[10][11] , upper and lower extremities [12][13] , umbilicus (Sister Mary Joseph nodule) [14] , trunk/abdominal wall [3][4][5]15] , and surgical incision/drain sites [16][17] . Prior authors have found that the occurrence of metastases to the skin generally implies terminal disease, with the average survival following diagnosis ranging from 3-6 months, even in cases where palliative chemo-and radiotherapy are administered [15] .…”
Section: Introductionmentioning
confidence: 99%